Housing Subsidies and Homelessness: A Simple Idea - Brendan O’Flaherty (The School of Public Policy Publications, 2012)
Reducing homelessness is an indisputable social good, and housing subsidies offer one way to do so. However, subsidies come in many different varieties and are intricately bound up with economic and social policies. This paper, written by one of North America’s leading urban economists, cuts through the tangle and argues that the simplest approach is the best. The ideal way to deter people from harmful acts is to reward them for abstaining. Thus, to combat homelessness, governments should offer housing allowances to people for every night they are not homeless. This optimal homelessness-reducing home allowance (OHRHA) is open to adjustment to suit individual circumstances and the effects of homelessness on different demographics. It is meant to reduce homelessness by aligning individual and societal incentives, forcing people to bear the consequences or realize the benefits that their actions impose on others. The author explores methods for financing OHRHA, examines means for tailoring it to meet the diverse needs of the homeless and discusses the policy’s effect on urban housing markets, all while comparing and contrasting the proposal to existing homelessness-reduction measures in Alberta, Canada and the US.